Factors Related to Health Promotion Behaviors of Village Health Volunteers in Selaphum District, Roi-Et Province - Wikol, Ratchanee; Vorapongsathorn, Sureepun; Wattanaburanon, Aimutcha; Chooratna, Kasem (Vajira Medical Journal : Journal of Urban Medicine, 2017)
Objective: To study the relationships between personal factors, predisposing factors, enabling factors, and reinforcing factors with health promotion behaviors among village health volunteers in Selaphum District, Roi-Et Province. Methods: This research was a cross-sectional descriptive study of 140 village health volunteers in Selaphum District, Roi-Et Province. Questionnaires were used as research instruments to collect data from the samples from January to March 2017. Statistical methods used to analyze the data were descriptive statistics, chi-squared test, and Pearson product-moment correlation. Results: Most village health volunteers were women, aged between 41-60 years and had received a secondary education or equivalent. Health promotion behaviors were at a moderate level. 1) Predisposing factors: knowledge of health promotion was at a high level, and attitude towards health promotion was at a moderate level. 2) Enabling factors: information received from various media was at a low level and access to health resources was at a high level. 3) Reinforcing factors: getting social support from various people was at a high level. Predisposing factors, enabling factors and reinforcing factors were correlated with total health promoting behaviors (p = 0.01), but personal factors were not. Some health promoting behaviors not correlated with predisposing factors, enabling factors and reinforcing factors were exercise promotion, accident prevention and inappropriate drug usage. Conclusion: Weakness in health promotion behaviors included exercise promotion, accident prevention and inappropriate drug usage. Health personnel should provide training activities for village health volunteers to support appropriate health behaviors.